2015
DOI: 10.1007/s10103-015-1771-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of anal fissure laser surgery: a pilot study

Abstract: Anal fissure is a common painful problem, affecting all age groups. Its pathophysiology is based on high sphincter pressures and reduced blood supplying and treatments which means that it generally reduces anal pressures and increases anodermal blood flow. Since each of the anal fissure's routine therapies has some limitations such as definite risk of permanent fecal incontinence and high recurrence rate, we tried to find a more effective and less invasive procedure. In this pilot study which was implemented o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…By analysing the literature about the use of laser technology in fissurectomy operations, we found that in 2015, an Iranian group had explored the use of CO2 laser for fissurectomy and fractional CO 2 laser for a multipoints myotomy of the internal anal sphincter (as an alternative to internal sphincterotomy), demonstrating an extremely rapid healing with no relapses at 1 year of follow-up ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…By analysing the literature about the use of laser technology in fissurectomy operations, we found that in 2015, an Iranian group had explored the use of CO2 laser for fissurectomy and fractional CO 2 laser for a multipoints myotomy of the internal anal sphincter (as an alternative to internal sphincterotomy), demonstrating an extremely rapid healing with no relapses at 1 year of follow-up ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Foi utilizado o Laser Fracionado de Dióxido de Carbono (COSCAN-5000, Korea) como terapêutica para os pacientes. Concluiu-se então que a laserterapia tem capacidade de diminuir a sintomatologia mostrada pelos pacientes, além de diminuir os riscos e os efeitos colaterais, diminuindo o tempo de recuperação e é um procedimento indolor (Esfahani, et al, 2015).…”
Section: Terapia a Laserunclassified
“…Numerous researches on the use of laser therapy for the treatment of tumors, anal fistulas, and hemorrhoids have been conducted in the last ten years. However, there are few researches on the use of laser therapy for acute anal fissures (8) .…”
Section: Introductionmentioning
confidence: 99%